Atomic-scale observation of strain-dependent reversible topotactic transition in La0.7Sr0.3MnOx films under an ultra-high vacuum environment. (December 2022) - Hu, Kejun; Zhang, Xinyu; Chen, Pingfan; Lin, Renju; Zhu, Jinlong; Huang, Zhen; Du, Haifeng; Song, Dongsheng; Ge, Binghui
Abstract: Reversible topotactic phase transition between perovskite (PV) and oxygen-vacancy-ordered brownmillerite (BM) structures provides an effective platform for realizing the control of physical properties in complex transition metal oxides. However, such reversibility always requires extreme external conditions, that is, a high temperature and vacuum environment during the PV-BM transition, while an oxidizing atmosphere and relatively low temperature vice versa. Here, we experimentally observe the reversible process in strained La0.7 Sr0.3 MnOx films at atomic scale by using in-situ heating aberration-corrected scanning transmission electron microscopy (STEM). Apart from the conventional reduction reaction of creating oxygen-vacancy-ordered frameworks after heating in the TEM, the inverse process of BM-to-PV transition is unexpectedly discovered under such an ultra-high vacuum atmosphere (∼10 −9 Torr) at room temperature. Moreover, this abnormal behavior is strain-dependent. The large compressive strain is found to be detrimental to the inverse phase transition. The density functional theory (DFT) calculations show that the high oxygen affinity of La0.7 Sr0.3 MnO2.5 is responsible for the reversible transitions. Our findings provide a new insight into the redox reactions of manganite and might be further utilized for potential applications in solid fuel cells, oxygen sensors or resistive switching memories. Graphical abstract: Image 1 Highlights: The reversible phase transitions of strained La0.67 Sr0.33 MnOx (LSMO) films were observed by using the in-situ heating STEM. The inverse process of BM-to-PV transition is unexpectedly discovered under such an ultra-high vacuum (∼10 −9 Torr) at RT. The large compressive strain is detrimental to the inverse phase transition owing to the large migration energy barrier.